2017
DOI: 10.1002/xrs.2767
|View full text |Cite
|
Sign up to set email alerts
|

Study of the uniformity of aerosol filters by scanning MA‐XRF

Abstract: Energy-dispersive X-ray fluorescence (XRF) is an attractive analytical method to determine the level of air pollution by heavy metals. The concentration of the filter in ng/cm 2 is obtained by direct comparison of the net characteristic line intensity of an element with that of a thin film standard. As the sampled area on the filter and the area of the standard are larger than the area analysed by the instrument, the distribution of the elements on the surface of both samples and standards have to be sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Correlation coefficients ( R 2 ) of each element were all higher than 0.98, manifesting the linearity of calibration curves. Because samples were considered as thin films, there were no matrix effects, and the relation between concentration and counts was linear . The limits of detection (LOD) for the EDXRF method is the minimum detectable concentration of elements that can be statistically discriminated from the background.…”
Section: Experiments and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation coefficients ( R 2 ) of each element were all higher than 0.98, manifesting the linearity of calibration curves. Because samples were considered as thin films, there were no matrix effects, and the relation between concentration and counts was linear . The limits of detection (LOD) for the EDXRF method is the minimum detectable concentration of elements that can be statistically discriminated from the background.…”
Section: Experiments and Methodsmentioning
confidence: 99%
“…Because samples were considered as thin films, there were no matrix effects, and the relation between concentration and counts was linear. [16] The limits of detection (LOD) for the EDXRF method is the minimum detectable concentration of elements that can be statistically discriminated from the background. It is calculated by the a (from calibration curve) plus three standard deviation of y-residuals, S y/x , [17] and the results are also given in Table 3.…”
Section: Calibration Experimentsmentioning
confidence: 99%
“…The production of certified reference filters is now planned. A sensitive scanning XRF system with a beam resolution of ~0.5 mm enabled 20 the spatial distribution of various elements across the surface of air filters to be examined. Application to commercially available Micromatter filter standards, widely used by XRFS laboratories that undertake air filter analysis, demonstrated that the distributions of elements were uniform to within 2%.…”
Section: Reference Materials and Calibrantsmentioning
confidence: 99%
“…On the other hand, for accurate XRF analysis, preparation of calibrating standard material that has similar elemental composition to actual aerosols is essential because XRF intensities of analyte are absorbed or enhanced by sample matrix or coexisting elements. Several preparation methods of standard material for the quantitative analysis of aerosol samples have been reported, such as microdroplet of aqueous solution, coprecipitation by diethyldithiocarbamate, nebulizing of aqueous solution, use of thin film reference materials, an aerosol generator, and a small chamber sampling . Among these methods, the microdroplet of aqueous solution is simplest technique for preparation of the aerosol standard material.…”
Section: Introductionmentioning
confidence: 99%